Is Zoom Dysmorphia a new disorder? - Pino, Olimpia (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: this editorial address the content of a recent letter about the main characteristic of Zoom dysmorphia phenomenon entitled “Zoom Dysmorphia: the rise of a new issue amidst the pandemic” that presents a compelling argument for conceptualizing this type of body dysmorphic disorder. Methods: It is largely known that self-appraisal, self-worth, and self-esteem are essential resources for an individual in private life and social context; a misperception of one’s own characteristic can influence behavior and modify some personality traits. In the present editorial it is examined the larger issue of the relationship with dysmorphic concern and appearance-focused behaviors together with the use of cosmetic interventions.Results: The coronavirus (Covid-19) pandemic increased popularity of videoconferencing has seen a massive shift toward virtual living where individuals found themselves staring at their own video scrutinizing their appearance and potentially developing dysmorphic concerns. Conclusions: This editorial explores the conceivable similarity between obsession problems and addictions suggesting several insights for buffering the effects of stress promoting coping and (re-) appraisal strategies (www.actabiomedica.it).